Talent Management And Job Performance In Nigerian Banking Industry: The Roles Of Work Engagement, Job Satisfaction And Perceived Support - Lukman, Jimoh Adams (2022)
The Central Bank of Nigeria aimed to reshape Nigeria’s banking industry. However, despite the various economic policies, most banks continue to perform poorly compared to their counterparts in other parts of the world. Therefore, there is a need to study the Nigerian banking industry, in particular, the predictors of employee job performance. Based on the social exchange theory and human capital theory, this study aims to investigate talent management and job performance of Nigerian banks, using work engagement and job satisfaction as mediators, as well as perceived organizational support (POS) and perceived supervisory support (PSS) as moderators. Questionnaire was used to obtain information from 302 full-time employees of the top five banks in Nigeria. PLS-SEM was used to analyze the data. The results indicated that talent attraction and talent development have a significant and positive influence on task performance, organizational citizenship behavior organization (OCBO), and organizational citizenship behavior individual (OCBI). However, talent retention was found to have no significant effect on employee task performance, OCBO, and OCBI.